Transosseous suture in situ repair treatment of a femoral anterior cruciate ligament avulsion fracture in a 30-year-old male patient: a case report and review of the literature - Liufu, Yifei; Hou, Muyuan; Xiao, Fangjun; Lv, Jiangfeng; Yang, Junxing (Frontiers in Surgery, 2025)
BackgroundAvulsion fractures typically occur at the tibial insertion site of the anterior cruciate ligament (ACL), while femoral ACL injuries usually involve midsubstance tears rather than bony avulsions. In previous case reports, femoral end avulsion fractures have been reported more often in skeletally immature patients.Case presentationIn this case report, we present a 30-year-old male patient who presented with a femoral-sided ACL avulsion fracture that was treated arthroscopically using a transosseous suture in situ repair technique. The avulsed fragment was surgically stitched back to its normal anatomical position. After the surgery, the patient followed a standard ACL rehabilitation program. Three-month postoperative MRI confirmed good ACL morphology. At the 1-year follow-up, the patient showed no signs of pain, motion limitation, or instability. Physical examination revealed an intact ACL, with normal results on axial shift and Lachman tests, indicating the effectiveness of the procedure.ConclusionThe transosseous suture in situ repair technique is an effective and precise treatment for ACL avulsion fractures. Its application should be considered based on the location of ligament injury and the integrity of the fragment.